1998
DOI: 10.1046/j.1365-2788.1998.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Rewards and gratifications among family caregivers: towards a refined model of caring and coping

Abstract: Supplemented by a case illustration, findings from a study in Wales are reported for the first time from the application of two new instruments for measuring rewards and stresses among family caregivers. The paper takes as its starting point a critique of models of caregiving which emphasize instrumental and pathological dimensions. Findings suggest that caregivers report the existence of pervasive rewards and gratifications, as well as stresses, as part of the caregiving experience, and that these stem from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 9 publications
6
114
0
5
Order By: Relevance
“…Previous studies on parents with children with special needs have often concentrated on the child's disability, looking at it from a crisis perspective. At the same time, however, there is also research suggesting that care giving might in itself be something rewarding (Grant et al 1998;Atkin and Ahmad 2000). Capturing the affected mothers' perspectives could thus raise important new knowledge and perspectives about living with and raising children with special needs, inspiring further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on parents with children with special needs have often concentrated on the child's disability, looking at it from a crisis perspective. At the same time, however, there is also research suggesting that care giving might in itself be something rewarding (Grant et al 1998;Atkin and Ahmad 2000). Capturing the affected mothers' perspectives could thus raise important new knowledge and perspectives about living with and raising children with special needs, inspiring further study.…”
Section: Discussionmentioning
confidence: 99%
“…Fyhr 2006). Yet, also other aspects have been brought up in research, such as that the needs of the child have contributed to the parents' own development or to a change in their perspective (Grant et al 1998;Atkin and Ahmad 2000). Recognizing this possibility may thus be considered as one of the resources of the mothers who took part in the present study.…”
Section: Children's Needs and Parental Responsibilitymentioning
confidence: 96%
“…This early body of work incorporated the positive feelings related to caregiving and the potential negative association with caregiver depression. This early research suggested that burden should not only be measured in terms of negative costs but in terms of positive benefits as well (Grant et al, 1998;Kramer, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, parenting a child with an intellectual disability may also be experienced positively (Grant, Ramcharan, McGrath, Nolan and Keady, 1998;Scorgie and Sobsey, 2000). Possible explanations for these contrasting experiences could include some parents having more effective coping strategies than others (Cummins, 2001).…”
Section: Parents' Viewsmentioning
confidence: 99%